Microstructure and corrosion performance of Al0.5FeCoNiCrMn coating prepared by plasma spraying mechanically alloyed powders. (3rd April 2022) - Mao, XingYe; Wang, YuXin; Jiang, Jie; Chi, YunLong; Dong, Yanchun; Yang, Yong; He, JiNing
ABSTRACT: In this work, Al0.5 FeCoCrNiMn coating is coated onto the surface of 316 stainless steel by plasma spraying Al0.5 FeCoCrNiMn powders prepared via mechanical alloying. The phase composition and microstructure of powders and coatings are analysed by X-ray diffraction, scanning electron microscopy, and transmission electron microscopy, respectively. The corrosion resistance of the coatings in 3.5 wt-% NaCl solution is tested with an electrochemical workstation, and the corrosion mechanism of the coating is analysed. The coatings are composed of BCC and FCC phases. The coating exhibits a higher corrosion potential and corrosion current density similar to that of 316 stainless steel. As the immersion time increases, the capacitive arc of the coatings and the charge transfer resistance increase.